2015
DOI: 10.1016/j.humpath.2015.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic adenocarcinoma up-regulated factor expression is associated with disease-specific survival in cervical cancer patients

Abstract: Pancreatic adenocarcinoma up-regulated factor (PAUF) is a novel soluble protein involved in tumor development and metastases. This study was to investigate the PAUF expression and its prognostic value in cervical cancer patients. The expression of PAUF was immunohistochemically determined in 345 formalin-fixed, paraffin-embedded cervical cancer tissues and 107 normal cervical epitheliums. Subsequently, its associations with clinicopathological characteristics and patient survival were assessed. PAUF protein wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Previous reports have revealed that PAUF nucleotide sequence is similar to that of common salivary protein 1 (LOC24220) in Homo sapiens . In the present study, we also observed PAUF expression in normal salivary glands.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previous reports have revealed that PAUF nucleotide sequence is similar to that of common salivary protein 1 (LOC24220) in Homo sapiens . In the present study, we also observed PAUF expression in normal salivary glands.…”
Section: Discussionsupporting
confidence: 86%
“…It accelerates tumour angiogenesis and activates TLR‐mediated ERK signalling to produce oncogenic cytokines and escape from innate immune surveillance in a paracrine manner . Immunostaining for PAUF is also detected in colorectal adenocarcinoma, cervical adenocarcinoma and SCC . However, little is known regarding the role of aberrant PAUF expression in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining of FGFR1, FGFR2, FGFR3 and FGFR4 was performed on 4-μm sections of the TMA and NCI60 cell microarray, as described previously [ 26 ]. In brief, following deparaffinization and dehydration, heat-induced antigen retrieval was performed for 20 min in an antigen retrieval buffer of pH 9.0 (for FGFR3 and FGFR4) or pH 6.0 (for FGFR1 and FGFR2) (Dako, Carpinteria, CA) using a steam pressure cooker (Pascal, Dako).…”
Section: Methodsmentioning
confidence: 99%
“…ANX immunohistochemical staining was performed using a standard streptavidin–peroxidase method, as described previously [ 29 ]. In brief, serial 4- μ m sections of the TMA were deparaffinized in xylene and rehydrated through a graded alcohol series.…”
Section: Methodsmentioning
confidence: 99%